Therapeutic Approaches in Mitochondrial Dysfunction, Inflammation, and Autophagy in Uremic Cachexia: Role of Aerobic Exercise - Yumei Zhang; Yuqing Liu; Xiao Bi; Chun Hu; Feng Ding; Wei Ding (Mediators of Inflammation)
Chronic kidney disease (CKD) causes several systemic changes, including muscular homeostasis, and eventually results in muscle atrophy. CKD-induced muscle atrophy is highly prevalent, and exercise is well known to enhance muscle function in these cases, although the exact mechanism remains unclear. Here, we aim to assess whether the protective effect of aerobic exercise in 5/6 nephrectomized (CKD) mice is associated with mitochondrial dysfunction, autophagy, or inflammation. C57BL/6J mice were randomly allocated into 3 different experimental groups: Sham, CKD, and CKD+aerobic exercise (CKD+AE). Renal function was assessed via serum creatinine and urea levels, and histological PAS and Masson staining were performed. Muscle wasting was determined based on grip strength, cross-sectional area (CSA), and MyHC protein expression. We also measured mitochondrial dysfunction in mice by assessing mtDNA, ROS, ATP production, and mitochondrial configuration. Autophagy was determined via assessments for Atg7, LC3, and SQSTM1 on western blotting. Inflammation was identified via proinflammatory cytokines and NLRP3 inflammasome components using real-time PCR and western blotting. We found that CKD mice exhibited higher BUN and creatinine levels and more severe glomerulosclerosis in the glomeruli and renal tubulointerstitial fibrosis, relative to the Sham group; all these effects were relieved by aerobic exercise. Moreover, grip strength, CSA, and MyHC protein expression were improved after 8 weeks of aerobic exercise. Furthermore, aerobic exercise significantly decreased MDA levels, increased SOD2 activity and ATP production, and improved mitochondrial configuration, relative to the CKD group. In addition, aerobic exercise downregulated the overexpression of proinflammatory cytokines and NLRP3 inflammasome components and balanced the mitochondrial biogenesis and autophagy-lysosomal system. Thus, we observed that aerobic exercise may ameliorate CKD-induced muscle wasting by improving mitochondrial dysfunction, inflammation, and autophagy-lysosomal system in uremic cachexia.